Improvement of the Professional and Methodical Training of Future Physics Teachers - Nyssan, G. (Jurnal Pendidikan IPA Indonesia, 2023)
The relevance of this study is conditioned by the fact that the law on education in the Republic of Kazakhstan was updated in 2020, which allows for considering the training of a future physics teacher from a new perspective. The purpose of this study is to develop and introduce instructional foundations for improving the system of professional and methodical training of future physics teachers in the Republic of Kazakhstan. Several models of this system are considered in detail: structural and multilevel. It has been proven that the basis of the system of methodical training for a future physics teacher is the course “Methods of teaching subjects (physics)”. For this purpose, the following research methods were used: analysis and synthesis, design, logical analysis, and the positions of scientific objectivity, systematisation in the study of the professional and methodical training of future physics teachers in the Republic of Kazakhstan. The paper provides a detailed description of the analysed discipline (goals, objectives, principles of choosing the content and design of pedagogical material, and features of the organisation of the educational process). This study provides vital insights into the development and implementation of improved training systems for future physics teachers in Kazakhstan. By focusing on both theoretical and practical aspects of teacher training and aligning them with labor market demands, it sets a precedent for creating more effective and adaptable educational frameworks. These advancements not only enhance the professional competencies of future physics teachers but also promise to elevate the quality of physics education in the region, ultimately contributing to the betterment of educational standards and practices.